DOP23 Long-term health consequences of COVID-19 in patients with Inflammatory Bowel Diseases – A Danish prospective population-based cohort study. (21st January 2022) - Attauabi, M; Dahlerup, J F; Poulsen, A; Hansen, M R; Vester-Andersen, M K; Eraslan, S; Prahm, A P; Pedersen, N; Larsen, L; Jess, T; Neumann, A; Haderslev, K V; et al.
Abstract: Background: The vast majority of patients with ulcerative colitis (UC) and Crohn's disease (CD) who acquire coronavirus disease 2019 (COVID-19) survive the infection. Still, the long-term health consequences of COVID-19 are not well described in patients with underlying inflammatory bowel disease (IBD). Methods: We conducted a population-based study investigating the outcomes of COVID-19 among patients with UC and CD in Denmark. The Danish COVID-19 IBD Database is an extensive population-based database which prospectively monitors the disease course of laboratory-confirmed COVID-19 among patients with UC and CD. Severe COVID-19 was defined as COVID-19 necessitating intensive care unit admission, ventilator use, or death, while adverse COVID-19 was defined as requirement of COVID-19 related hospitalization. Sequelae following COVID-19 were defined as symptoms that developed during or after an infection consistent with COVID-19, were present for more than 12 weeks, and were not attributable to alternative diagnoses. Results: The study included 319 patients with UC and 197 patients with CD from January 28 th, 2020, to April 1 st, 2021. Of these, a total of 137 (42.9%) and 85 (43.1%), respectively, participated in a subsequent investigation of post-COVID-19 sequelae after a median of 5.1 months (IQR 4.5–7.9) after infection (Table 1). An equal proportion of patients with UC (58 (42.3%)) and CD (39 (45.9%), p= 0.60) reported persisting symptoms of COVID-19 for at least 12 weeks, consistent with the development of post-COVID-19 syndrome. The most common persisting patient-reported symptoms included fatigue (UC: 49 (35.8%), CD: 31 (36.5%), p= 0.92), anosmia (UC: 37 (27.0%), CD: 25 (29.4%), p= 0.70), ageusia (UC: 26 (19.0%), CD: 24 (28.2%), p= 0.11), headache (UC: 19 (13.9%), CD: 16 (18.8%), p= 0.32), dyspnea (UC: 19 (13.9%), CD: 16 (18.8%), p= 0.32), and arthralgia (UC: 17 (12.4%), CD: 14 (16.5%), p= 0.40) (Figure 1). Only discontinuation of immunosuppressive therapies for UC during COVID-19 (OR=1.50 (95% CI 1.07–10.22), p= 0.01) and the severity of COVID-19 among patients with CD were independently associated with the long-term effects of COVID-19 (OR=2.76 (95% CI 1.05–3.90), p= 0.04) (Tables 2–3). Conclusion: This Danish population-based study found a high occurrence of patient-reported persisting symptoms following the acute phase of COVID-19 infection, which were associated with the discontinuation of immunosuppressive therapies for UC during COVID-19 and the severity of COVID-19 among patients with CD. These findings might have implications for planning the healthcare of patients with inflammatory bowel diseases in the post-COVID-19 era.